Health benefit from decreasing exposure to heavy metals and metalloid after strict pollution control measures near a typical river basin area in China. (October 2017) - Cao, Suzhen; Duan, Xiaoli; Ma, Yingqun; Zhao, Xiuge; Qin, Yanwen; Liu, Yan; Li, Sai; Zheng, Binghui; Wei, Fusheng
Abstract: The metal(loid) pollution still is a great concern due to the effects from urbanization and industrialization. While, the health risks from the toxic metal(loid)s could decrease if strict pollution control measures were adopted. However, few studies to date investigate the health risks of heavy metal(loid)s in a systematic river basin for the dependent residents, after taking pollution control measures. Thus, the contents of metal(loid)s (Cu, Pb, Zn, Cd, Mn, As) in surface water along a typical river basin were investigated in this study, and the potential non-carcinogenic and carcinogenic health risks posed to the residents were assessed. Although the soluble contents of Cu, Pb, Zn and Cd exceeded the respective thresholds in two sites located downstream the mine area, they were greatly decreased in comparison with previous contamination levels, and the soluble concentrations of all the metal(loid)s were within the relevant thresholds in the sites far away from the mining area. Moreover, the closer to the mining area, the higher the pollution levels of metal(loid)s. The total hazard index for non-carcinogenic risks of metal(loid)s were basically lower than the threshold (1) for the local population. Whereas, although the content of metal(loid)s were low (such as As), they could pose relative higher non-carcinogenic health risks. The result illustrated that pollution levels, toxicity of the contaminants and exposure behavior patterns all could contribute to the potential detrimental health risks. Additionally, the non-carcinogenic and carcinogenic risks from ingestion exposure were ∼2–∼4 orders of magnitude higher than those from dermal contact. The total carcinogenic risks were basically lower than the maximum tolerable levels (1.0 × 10 −4 ), indicating carcinogenic risks from most areas of the river could also be accepted. Among different population groups, heavy metal(loid)s posed relative higher non-carcinogenic and carcinogenic risks to the children in 0–5 years old. Fortunately, the surface water in most area of this basin is safe in usage for the local population and the health risks were basically acceptable in case exposed to the target metal(loid)s, after the river basin was in the charge of strict pollution control measures. Graphical abstract: Highlights: The contents of heavy metal(loid)s in various sites are observed along a typical river basin. The health risk assessments of local children and adult are analyzed. The water quality is not heavily polluted by heavy metal(loid)s. Ingestion exposure is the predominant pathway for the local population exposed to metal(loid)s. Health risks are generally acceptable, but risks were highest for the children (0–5 yrs).